The Role of a Complex Task in a Physics Lesson - Zhonzholadze, Nino (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
For certain period of time, the school was switched to distant learning. Less communication, systemic and uncontrolled usage of computer technologies, the necessity of using own opportunities less effected on students’ motivation directly. The lack of motivation is reflected on learning outcomes and students’ achievements. Age peculiarities and above mentioned factors especially effected on 9th grade students who had difficulties to match everyday interests and routine learning process with each other. For me as a physics teacher, the most interesting was to find the answer to the following question-how the students can see physics laws in the phenomenon taking place in the world and solve various life problems with the attained knowledge and because of this I offered the class to work on complex task “Tires“. In the process of working on complex tasks I took into consideration students’ needs, individual peculiarities and used differentiated approach. This helped students to comprehend the issue in depth. I constantly monitored the process and in case of need I gave feedback to students and the whole class about process improvement. I used formative assessment to evaluate the students. The complex task was funny, the students had to see the laws of physics and use the acquired knowledge to solve specific life problems. The complex task aroused the interest in students and increased their interest in physics learning. Progress in results gave me the chance to make such conclusion: Complex tasks help students to see the need to use theoretical knowledge in real life and help teachers to increase students' motivation and knowledge